Geochemical and mineralogical characteristics of beach sediments along the coast between Alanya and Silifke (southern Turkey). (2nd January 2018) - Yalcin, M.G.; Setti, M.; Karakaya, F.; Sacchi, E.; Ilbeyli, N.
Abstract: The aim of this work was to determine the distribution of trace metals in the coastal sediments from the area between Silifke and Alanya (Turkey) and to investigate the sources of these elements, based on their mineralogical, petrographical and geochemical characteristics. Forty three samples were analysed for the determination of their water content, grain-size distribution, petrographical features and their chemical and mineralogical compositions. The samples had low water content, in agreement with the large sand grain size. The mineralogical composition reflects the complex geological setting of the area. The most abundant mineral phases are represented by calcite and dolomite, followed by quartz and mica. Chlorite, feldspar and other carbonates are present in lesser amounts, while kaolinite was detected in one sample only. All samples contain hematite, chromite, magnetite and goethite and one sample contained pyrite. Samples with high concentrations of trace metals, contained fragments of metamorphic rocks with pyroxene, amphibole, quartz and feldspar, whereas carbonates and opaque minerals were subordinate. Compared to literature data, the average concentrations of several elements and trace metals were great enough to be considered as possibly toxic, exceeding the Turkish higher acceptable limits. Geochemical data were treated statistically using Principal Component Analysis (PCA) to obtain evidence of their distribution and to identify any correlations. Based on the distribution of mineral phases, the area investigated was divided into different provinces, each characterized by the abundance of one, or more, tracer minerals. In the westernmost areas, between Alanya and Demirtas, the sediments indicate a provenance from dolomites or marbles. In the area between Demirtas and Gazipasa the provenance was from quartzites, clastic and metamorphic rocks and in the sector between Guney and Anamur, the sediments were derived mostly from low-grade metamorphic rocks, in particular metaschists and metabasites. The sediments in the area between Anamur and Ovacik, display variable source rocks and those between Ovacik and Silifke, were derived from limestones and, subordinately, clastic rocks. The trace-metal concentrations in beach sands appear to be related to the abundance of silicate minerals derived from weathering of the metamorphic-rock outcrops in the inland mountainous regions. In contrast, the trace-metal contents of the limestone- and dolomite-bearing beach sands were small.